Challenges Based on Antiplasmodial and Antiviral Activities of 7‐Chloro‐4‐aminoquinoline Derivatives. (8th February 2023) - Mizuta, Satoshi; Mosaddeque, Farhana; Tun, Mya Myat Ngwe; Teklemichael, Awet Alem; Taniguchi, Mayumi; Hosokawa, Masashi; Yamaguchi, Tomoko; Makau, Juliann; Huy, Nguyen Tien; Mizukami, Shusaku; Nishida, Noriyuki; Morita, Kouichi; et al.
Abstract: We report the structural functionalization of the terminal amino group of N 1 ‐(7‐chloroquinolin‐4‐yl) butane‐1, 4‐diamine, leading to a series of 7‐chloro‐4‐aminoquinoline derivatives, and their evaluation as potent anti‐malarial and anti‐viral agents. Some compounds exhibited promising anti‐malarial effects against the Plasmodium falciparum 3D7 (chloroquine‐sensitive) and Dd2 (chloroquine‐resistant) strains. In addition, these compounds were assayed in vitro against influenza A virus (IAV) and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Compound 5 h, bearing an N ‐mesityl thiourea group, displayed pronounced anti‐infectious effects against malaria, IAV, and SARS‐CoV‐2. These results provide new insights into drug discovery for the prevention or treatment of malaria and virus co‐infection. Abstract : Chloroquine (CQ) has displayed the potential to inhibit malaria and virus infections. We designed and synthesized 7‐chloro‐4‐aminoquinoline derivatives, which were synthesized and evaluated for their antiviral and antimalarial properties. Most of these compounds exhibited promising antimalaria activity and anti‐influenza virus activity. The thiourea compound 5 h with a mesityl group exerted better anti‐SARS‐CoV‐2 activity (IC50 =0.16 μM) than CQ.